2004
DOI: 10.1111/j.1468-0408.2004.00186.x
|View full text |Cite
|
Sign up to set email alerts
|

‘Performance’ Without Pay? Managing School Budgets Under Performance Related Pay: Evidence from the First Year of PRP

Abstract: :  This paper reports research in ten secondary schools in London and East Anglia on the first year of the performance related pay (PRP) scheme for teachers introduced by the (UK) Labour Government. It focuses on tensions between the resultant additional claims on school budgets created by PRP and the Government's refusal to guarantee that such additions to the pay bill will be centrally funded on a long‐term basis. The research involved semi‐structured interviews with heads and staff with specific responsibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 21 publications
0
7
0
1
Order By: Relevance
“…Plans to introduce greater financial incentives to stimulate greater activity from doctors are seen as too limited (Maynard and Bloor, 2004), as misguided (Flint, 2004) and as unworkable (Skilton, 2004). 5 The difficulties of this approach in education have been discussed at length by Cutler and Waine (2004). Indeed, as the difficulties of managing public enterprises present a significantly more challenging order of difficulty for managers (Metcalfe, 1993) and there is evidence of the adverse consequences (short term focus, imprecise measures of human capital) of payment by results systems in the private sector (Widener, 2006), it should not be a surprise that difficulties are encountered with incentive systems in the more complex setting of the public sector.…”
Section: Mechanisms Of Changementioning
confidence: 99%
“…Plans to introduce greater financial incentives to stimulate greater activity from doctors are seen as too limited (Maynard and Bloor, 2004), as misguided (Flint, 2004) and as unworkable (Skilton, 2004). 5 The difficulties of this approach in education have been discussed at length by Cutler and Waine (2004). Indeed, as the difficulties of managing public enterprises present a significantly more challenging order of difficulty for managers (Metcalfe, 1993) and there is evidence of the adverse consequences (short term focus, imprecise measures of human capital) of payment by results systems in the private sector (Widener, 2006), it should not be a surprise that difficulties are encountered with incentive systems in the more complex setting of the public sector.…”
Section: Mechanisms Of Changementioning
confidence: 99%
“…Here, it was the senior management teams rather than the governors who were involved in these areas. This finding is also evident in the introduction of performance related pay in schools where headteachers were more involved in this than governors (Cutler and Waine, 2004). Harrison’s (1998: 147) work on NHS boards concluded that ‘despite initiatives to improve the corporate performance and accountability of the boards of NHS bodies … boards appear to take inadequate steps to secure successful policy implementation and remain unclear about the ambivalence towards matters of accountability’.…”
Section: Accountability and Theatrical Performancesmentioning
confidence: 90%
“…I den offentlige sektor er der typisk begraensede midler til performance-relateret løn (Perry 2009;Marsden & Richardson 1994;Makinson 2000;Cutler & Waine 2004). Det kan derfor vaere vanskeligt at imødekomme selv berettigede forventninger til performance-relateret afl ønning, for selv om performance øges, følger midlerne til større løn ikke nødvendigvis med.…”
Section: Hindringer For Fairness I Den Offentlige Sektorunclassified